(untitled) (Journal of the College of Education for Women, 2019)
Abstract:This investigation was carried out to study the nutritional adequacy forinfant milk formula, which imported by Iraqi Ministry of Trade, and areavailable in local markets .Most of these formulas contained nearly the samecomposition of nutrients which are ,Matines ,Sunny Boy , Salsabeel AL- Badie,Moroug, ,Charton ,Materna Lery Celia ,Lacstar Lailac,Nactalia. yet they areunbalanced for providing the daily nutritional requirements for infants whomdepend on bottle feeding for six times daily in their first six month of age. Asthere were an increase in daily intake for protein content and most vitaminsthat included D, E, C, B1, B2, Niacin, B6, B12, and Biotin as well as mostminerals namely Calcium, Phosphorus, Magnesium, Sodium, Potassium,Chloride, Manganese, Cooper, Iron and Zinc .While there were a drop in dailyintake in energy as well as, in fat, carbohydrate, and some vitamins such asA, Folic acid, Choline and some minerals such as Iodine, Selenium. Oncomparing the daily intake of infants with the dietary recommended intake(DRIs) there were a significant differences among all values.